2017
DOI: 10.1080/21645515.2017.1363133
|View full text |Cite
|
Sign up to set email alerts
|

Approaching a decade since HPV vaccine licensure: Racial and gender disparities in knowledge and awareness of HPV and HPV vaccine

Abstract: There was evidence of disparities in HPV and HPV vaccine awareness among men compared with women and non-Hispanic Blacks and Hispanics compared with non-Hispanic Whites. To foster improvements in HPV vaccine uptake and reduce disparities in HPV associated cancers, future interventions must target men and minority populations, for whom knowledge gaps exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 48 publications
(64 reference statements)
10
62
2
Order By: Relevance
“…Nevertheless, this study found that awareness of HPV (62.5%) and the HPV vaccine (58.3%) was significantly lower among fathers than mothers. Prior studies conducted in the US have also found awareness of HPV and the HPV vaccine among other racial/ethnic parents to be lower than the 80% target level set by the Healthy People 2020 [38][39][40][41]. Moreover, similar to our findings, these prior studies also documented that mothers are more likely than fathers to be aware of HPV and the HPV vaccine [38][39][40][41].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, this study found that awareness of HPV (62.5%) and the HPV vaccine (58.3%) was significantly lower among fathers than mothers. Prior studies conducted in the US have also found awareness of HPV and the HPV vaccine among other racial/ethnic parents to be lower than the 80% target level set by the Healthy People 2020 [38][39][40][41]. Moreover, similar to our findings, these prior studies also documented that mothers are more likely than fathers to be aware of HPV and the HPV vaccine [38][39][40][41].…”
Section: Discussionsupporting
confidence: 88%
“…Study findings found that 76.8% of parents had heard of HPV and 75% had heard of the HPV vaccine. These findings indicate that although awareness of the HPV vaccine in this group of Central American immigrant parents is lower than the target level set by the Healthy People 2020 (80%) [12], it is higher than that reported for the full US population (66%) [38]. Nevertheless, this study found that awareness of HPV (62.5%) and the HPV vaccine (58.3%) was significantly lower among fathers than mothers.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…how providers recommend the HPV vaccine. 15,53,54 In this study, higher percentages were reported if the respondent was female and if they had a female child aged ≥15 years old. Healthcare providers may recommend HPV vaccination less frequently to parents / guardians of male children.…”
Section: Reasons For Low Vaccination Ratesmentioning
confidence: 56%
“…12,13 Although routine HPV vaccination has been recommended in the United States (US) since 2006 for females and 2011 for males ages 9-26 years, 14 disparities in knowledge and awareness about HPV and the HPV vaccine persist, and vaccination rates remain suboptimal. 15 The Healthy People 2020 goal is to have 80% HPV coverage among 13-15-year-olds. 16 In the US, HPV vaccine completion rates are low for girls and boys ages 13-17 (49.5% and 37.5%, respectively).…”
Section: Introductionmentioning
confidence: 99%